HUBUNGAN TINGKAT PENGETAHUAN TENTANG HIPERTENSI DENGAN UPAYA PENCEGAHAN KEKAMBUHAN HIPERTENSI PADA LANSIA - Arya Munang Ayu Priyadarsani; I Nyoman Sutresna; I Gede Wirajaya (Media Keperawatan:Politeknik Kesehatan Makassar, 2021)
Hypertension is an increase in blood pressure that exceeds normal limits and can result in death. Lack of knowledge affects hypertensive patients to be able to overcome hypertension recurrence. This study aims to determine the relationship between the level of knowledge about hypertension and the prevention of hypertension recurrence in the elderly.This study used quantitative methods with descriptive research design and cross sectional approach with nonprobability sampling with total sampling, where the sample size was 42 elderly respondents with hypertension at Puskesmas II Denpasar Utara.The results showed that knowledge about hypertension was in a good category (54.8%), efforts to prevent hypertension recurrence by category had been carried out (73.8%). Chi Square test results show p value = 0,000 so that p value ≤ 0.05, so Ho is rejected and Ha is accepted so that there is a relationship between the level of knowledge about hypertension and efforts to prevent hypertension recurrence in the elderly.Knowledge about hypertension has an impact on the elderly to encourage the desire to prevent hypertension recurrence. This research is expected to provide information to patients with hypertension about the importance of prevention efforts by increasing knowledge about hypertension.